Analisis Kandungan Asam Retinoat Pada Krim Anti Jerawat Di Toko Kosmetik X Pasar Jodoh - Diani Mega Sari; Eka Febriyanti; Ghalib Syukrillah Syahputra; Annisa Laili Oktaviyani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Growth from adolescence to adulthood is a transition that causes many hormonal changes, both physical, psychological and social. This change will cause health problems, one of which is on the face, namely Acne vulgaris (AV). Retinoic acid is one of the chemicals that is prohibited for use because it can cause dry skin, burning, teratogenicity (fetal defects)0and skin cancer. The aim of this research was to find out whether the acne cream in the cosmetic shop x Pasar Jodoh contained retinoic acid, and to determine the levels of retinoic acid in the samples. There were 10 acne cream samples studied. The qualitative test of retinoic acid uses the thin layer chromatography (TLC) method observed under UV 254 light. And the quantitative test uses the UV-Vis Spectrophotometry method. Spectrophotometric determination of retinoic acid levels at a wavelength of 340 nm. The results0obtained by the thin layer chromatography (TLC) method were that sample B was positive for retinoic acid and the results from the UV-Vis spectrophotometry0method were 0.0005%.